The Effect of COVID – 19 on Academic Achievement of Senior Secondary School Students in English Language - Cyprian NWOKOCHA, Azubuike; Elijah ETUKUDO, Udobia (International Journal of English Language Education, 2022)
The effect of COVID – 19 pandemics pandemic on the academic achievement of senior secondary school students in the rural communities of Akwa aibom state of Nigeria was studied. Five hundred (500) students were randomly selected from 2057 Senior Secondary School Class Two (SSC2) students. The scores of the students in English Language were collected from the terminal examination result broad sheets. Using causal comparative (ex- post facto) design, the analysis of data revealed that there existed significant differences in academic achieve of the students before and after the COVID – 19 pandemics. students’ achievement decline after COVID -19, due to the negative effect of the pandemic on learning and education in general. Students need palliatives and motivations to recover from shock cause by the COVID – 19.